Du réalisme dans l’analyse économique des conflits d’usage : les enseignements de l’étude du contentieux dans trois départements français (Isère, Loire-Atlantique, Seine-Maritime) - Thierry Kirat; Romain Melot (Développement Durable et Territoires)
On Realism in the Land-Use and Environmental Conflicts: Lessons from an Analysis of Courts Rulings in Three French Territories (Isère, Loire Atlantique, Seine Maritime). Land-use and environmental conflicts reveal the existence of antagonism between individual or collective preferences on space and natural resources allocation to alternative uses. Such conflicts are grounded on various negative external effects which are provoked by the combination of different uses (agricultural, industrial, residential, touristic, etc.) in a proximity pattern. Environmental conflicts in particular are a significant example of the growing conflictuality between ecologist associations, farmers, and neo-rural people in periurban settings. The article focuses on an issue to which economic theory tends to pay little attention, namely the legal dimension of land-use and environmental conflicts. The paper scrutinizes the conflicts which are translated into the legal language before civil and administrative courts. The empirical analysis centres on three French departments. The empirical, inductive, and institutional methodology followed aims at a realistic understanding of conflicts such as the courts resolve them. The article ambition is to provide a characterization of the nature of conflictuality within the three territories investigated. It also aimed at determining if the proximity linked conflicts are decided by courts in a territorialized perspective.